A fatal disseminated cryptococcal infection in a patient treated with zanubrutinib for Waldenström's macroglobulinemia. (December 2022) - Patel, Dave; Sidana, Megan; Mdluli, Xolani; Patel, Vallari; Stapleton, Ann; Dasanu, Constantin A
Introduction: Zanubrutinib is a second generation, irreversible small-molecule Bruton tyrosine kinase inhibitor (BTK) approved for the treatment of Waldenström's macroglobulinemia, mantle cell lymphoma, and marginal zone lymphoma. As a class, BTKs have been linked with an increased risk of respiratory infections in clinical trials. Case Report: We describe a 75-year-old patient who presented with generalized weakness, fevers, dyspnea, and dry cough four months after starting zanubrutinib therapy for Waldenström's macroglobulinemia. He was subsequently diagnosed with pneumonia. Septic work-up led to diagnosis of disseminated cryptococcal infection, complicated by fungal pneumonia and meningitis. Management and outcome: Zanubrutinib was held on admission, and the patient was started on combination oral and intravenous antifungal therapy. Despite clearance of fungemia, aggressive resuscitation, and appropriate antimicrobial therapy, respiratory status deteriorated requiring intubation. His condition progressed to septic shock, multiorgan failure, and demise. Discussion/Conclusion: We report herein a case of fatal disseminated cryptococcosis in the setting of zanubrutinib use for Waldenström's macroglobulinemia. At the time of diagnosis, his Waldenström's macroglobulinemia was in a partial response. The mechanism by which Bruton tyrosine kinase inhibitors (BTKs) lead to invasive fungal infections in these patients remains to be explored. T- and B-cell immune defects accompanying low-grade B-cell lymphomas may contribute to the severity of these infections.